GROWTH RESPONSE AND NUTRIENT UTILISATION OF AFRICAN CATFISH Clarias gariepinus FED Cucumeropsis edulis SEEDMEAL - OLAWEPO, K.D; JIMOH, W.A; BANJO, O.T; FAWOLE, W.O; IDOWU, C. F. (Nigerian Journal of Fisheries, 2019)
A feeding trial was conducted to evaluate the growth response and nutrient utilisation of Clarias gariepinus juveniles fed Cucumeropsis edulis meal as replacer for soybean meal. Five diets (40% Crude protein) containing soybean which was replaced by Cucumeropsis edulis at a rate of 0%, 7.5%, 15%, 22.5% and 30% were formulated. C. gariepinus juveniles of an average weight of 10.0±0.07g was stocked in ten plastic bowls at 10 fish per bowl replicated in a completely randomized design and fed at 5% body weight twice daily for 56days. Significant variation (P<0.05) existed in weight gain, specific growth rate; feed conversion, and survival rate among the fish fed various dietary treatments. There was no significant difference (P>0.05) in all the parameters between fish fed diet 1 and diet 2. A decrease in growth and nutrient utilization parameters of fish fed various dietary treatments was observed as the level of Cucumeropsis edulis seed meal increased. The results show that it is possible to replace soybean meal in the diet of Clarias gariepinus juveniles with soaked Cucumeropsis edulis meal, with optimum growth response at 15% replacement level. It is recommended that other processing techniques be employed in removing the antinutrients in Cucumeropsis .edulis. Keywords; , , ,